Demonetisation as an Economic Policy Tool: Macroeconomic Implications of a Monetary Market Shock. The Example of the Indian Monetary Reform - Roy, Sebastian Amit (Dynamic Econometric Models, 2019)
This paper discusses the implementation of the 2016 India demonetisation, and analyses its macroeconomic consequences. The pivotal issue here is a regional heterogeneity of CPI inflation caused by demonetisation. A dynamic panel CPI model has been estimated in order to find out whether unequal accessibility of banking services determines the inflation heterogeneity. The findings suggest that financial services accessibility is not a significant inflation-driving factor. Hence a hypothesis about a redistribution of wealth between rural and urban areas with different access to banking might be rejected.